Tales of wisdom & wonder - Lupton, Hugh (Barefoot Books, 1998)
A collection of seven tales from around the world featuring remarkable animals and extraordinary people reminding us of how vast and mysterious the world is and how our lives can be transformed in the most unexpected circumstances.